Royal Flying Doctor Service. [Season 1] [videorecording (DVD)] - Meadows, Ian, 1983-; Banks, Imogen; Fennessy, Mark (PBS Distribution, 2021)
Based on remarkable real-life stories, this gripping drama series follows the modern-day heroes of the Royal Flying Doctor Service as they navigate private lives as turbulent and profound as the heart-stopping emergencies they attend to across some of the most beautiful and inhospitable places in the Australian outback.